Employers Size Wage Differential: Does Investment in Human Capital Matter? (The Pakistan Development Review, 2009)
Wage differential due to employer size is one of the key areas of interest in labour market research because a strong positive relationship between employer size and wages has been observed in developed and developing countries. It is, however, relatively neglected area of research in Pakistan. The purpose of present study is to investigate the employer size wage differential by looking at human capital factors. The study is based on standard methodology and estimates earning functions on Labour Force Survey (LFS) data for year 2007-08. Results clearly show that human capital investment has a bigger role in determining wages in the larger firms as compared to smaller firms. The main policy implications emanating from the analysis are the higher investment in skill which increases opportunities for workers in the labour market for higher wages and for jobs with good characteristics especially in large sized firms. The government policy towards education and skill formation needs serious reforms and better allocation of funds so that people get chance to enhance their skill level hence wages. JEL classification: J31, J40, J24 Keywords: Wage Differential, Human Capital, Labour Market